Effect of in-situ variability of soil on seismic design of piled raft supported structure incorporating dynamic soil-structure-interaction. Issue 84 (May 2016) - Das, Biplab; Saha, Rajib; Haldar, Sumanta
Abstract: Inherent variability of soil considerably affects the seismic design of piled raft supported structures. Conventional design of such structure adopts fixity at base level of superstructure and pile head. However, soil–pile–superstructure interaction largely affects the fundamental frequency and design forces in columns and piles. In contrast, fixed base assumption cannot capture soil structure interaction (SSI) effect. In addition, uncertainty in soil may further leads to a change in the dynamic behavior of the system. This study examines the effect of inherent variability of undrained shear strength of soil in seismic design of structures supported by piled raft foundation embedded in soft clay. Superstructure is modeled as lumped mass stick model and piled raft slab is modeled as rigid plate. Pile is modeled as Euler–Bernoulli beam element and soil resistance is modeled using linear Winkler springs attached to the pile. Dynamic analysis is carried out in time domain to estimate the responses. Monte Carlo simulation technique is used for probabilistic assessment of the fundamental frequency and forces at column and pile attributing a wide range of parametric variation of a representative soil–piled raft–superstructure system. The study shows that the fundamental frequency and forces in column and pile changes significantly due to soil variability. Highlights: Sustainable design solution of soil-piled raft-structure system is addressed. Effect of in-situ variability along with SSI on design response is investigated. Monte-Carlo simulation is used for probabilistic analysis. Parametric study is performed to see the influence of various parameters. Probability of failure of pile foundation is calculated for both limit state criteria.